IMPLEMENTASI INTEGRASI KURIKULUM 2013 DAN MERDEKA BELAJAR DI SDIT AL FITRAH KOTA BANDUNG - Aneka Ahmadi; Aceng Ali Nurdin; Ishmahani Sobarningsih; Asep Herry Hernawan (Universitas Tanjungpura, 2023)
Education has a goal to create a generation that is intelligent and has good character. This study aims to describe the implementation of the Education Unit Level curriculum, K-13 or the Operational Curriculum of the SDIT Al-Fitrah Driving School in Bandung, which is based on KSDIT-AF Number 54 of 2021 and in accordance with the guidelines for developing KTSP in accordance with Permendikbud no. 81a of 2013 and This year's Al Fitrah SDIT curriculum adheres to the 2013 Curriculum. Using a qualitative descriptive approach. The object being observed is SDIT Al-Fitrah in Bandung. Data in the form of documents. The research strategy uses content analysis. The results showed that the curriculum design at SDIT Al-Fitrah Bandung was designed with various patterns, including the use of a curriculum structure that applies to all general subjects and Mapel Mulok Khas Islam Terpadu for all classes. Supporting curriculum such as intracurricular, curricular and extracurricular. Then regarding implementation guidelines in the form of priority programs, self-development and life skills education. As for the implementation of independent learning, SDIT Al-Fitrah Bandung has only implemented it in grades I and IV of the Driving School Program.